ANALISIS PENGARUH GAYA BELAJAR TERHADAP KEAKTIFAN BELAJAR FISIKA PADA SISWA KELAS X IPA SMAN 11 MUARO JAMBI - Astiara Steviana; Maison .; Dwi Agus Kurniawan; Azfin Gustria (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT Student learning activities are activities or activities of students in learning in the form of activities with themselves or groups that are influenced by internal and external factors. Learning style is a way that students use to understand information so that it can be accepted easily. In learning physics, student activity is very necessary. So that learning in the classroom needs to be carried out according to the student's learning style in order to create an active learning atmosphere and students can easily understand the material presented. This study aims to determine the effect of learning styles on the activeness of learning Physics in students. This research is a type of qualitative research. The data collection technique used is interviews with informants, namely Physics subject teachers in class X. From the results of interview analysis, it is known that students of class X IPA SMAN 11 Muaro Jambi have a type of visual learning style. This is because students are more interested and faster to learn if they use video media by raising the latest issues in Physics learning. However, for student activity is low. From the results of the interviews, it is known that students are not actively involved in learning such as asking questions. The low level of student activity is caused by several factors. The use of models or learning methods that are in accordance with students' learning styles can help maximize the learning process. So that the learning process can run actively and planned and provide maximum results. Keywords: Learning activity, Learning style, Physics